System Quality and User Adoption of Coretax in Indonesia: A PLS‑SEM‑Based Technology Acceptance Model Study - Pawitri, Ni Made Puspa; Anggara, I Wayan Gde Wahyu Purna (E-Jurnal Akuntansi, 2025)
This study aims to analyze the effect of system quality on user acceptance of the information technology–based tax administration system (Coretax) at the Directorate General of Taxes, Indonesia. System quality is assessed through reliability, responsiveness, security, availability, and interoperability. Employing a quantitative approach, data were collected via a questionnaire distributed to 97 Coretax users across various Tax Service Offices. Data analysis was performed using Partial Least Squares Structural Equation Modeling (PLS‑SEM). The results indicate that system quality has a positive and significant impact on perceived ease of use and perceived usefulness, which in turn influence users’ behavioral intention to use Coretax. This behavioral intention was found to have a positive and significant effect on actual Coretax usage. Practically, the study recommends that tax authorities continually enhance the system’s technical quality to ensure the sustainable adoption and utilization of Coretax. Keyword: System Quality, Technology Acceptance Model (TAM), Coretax, E‑Government Adoption